A Literature Review: Practical Implications Of Organizational Theories On Organizational Effectiveness - Rama Dani; Ivansyah Hafif Harahap; Insyiah Al Ares; Rony Edward Utama (Jurnal Mirai Management, 2025)
This literature review aims to evaluate the practical implications of organizational theories on organizational effectiveness across three strategic sectors: education, Hajj and Umrah services, and healthcare. Using a qualitative, library-based research approach, the study analyzes scientific literature focusing on four major frameworks: Contingency Theory, Complexity Theory, Open Systems Theory, and Institutional Theory. The findings indicate that applying these theories significantly enhances organizational effectiveness. Contingency Theory emphasizes aligning organizational structure and leadership styles with situational factors; Complexity Theory explains organizational adaptation to rapid changes and non-linear interactions; Open Systems Theory highlights the importance of resource exchange and feedback with the external environment; while Institutional Theory underscores the influence of norms, values, and legitimacy in sustaining organizational performance. In the education sector, these theories guide curriculum management and service quality improvement. In the Hajj and Umrah sector, practical implications include strengthening coordination, innovation, and regulatory compliance. In healthcare, they guide responsive and quality-oriented service systems. The article proposes a conceptual model integrating the four theories as a strategic framework to enhance organizational effectiveness across sectors.